Information Security : 18th International Conference, ISC 2015, Trondheim, Norway, September 9-11, 2015, Proceedings - Lopez, Javier; Mitchell, Chris J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 18th International Conference on Information Security, ISC 2015, held in Trondheim, Norway, in September 2015. The 30 revised full papers presented were carefully reviewed and selected from 103 submissions. The papers cover a wide range of topics in the area of cryptography and cryptanalysis and are organized in the following topical sections: signatures; system and software security; block ciphers; protocols; network and cloud security; encryption and fundamentals; PUFs and implementation security; and key generation, biometrics and image security. .
Keywords: Computer security; Data encryption (Computer science).; Computer software; Computer science; Software engineering; Systems and Data Security; Cryptology; Algorithm Analysis and Problem Complexity; Math Applications in Computer Science; Special Purpose and Application-Based Systems; Computers and Society